STUDI KASUS: EVALUASI DAN STRATEGI DESAIN RUMAH HUNIAN UNTUK ORANG TUA PENSIUNAN - Dewanda, Graciani Cahyadresta; Ima Defiana (Nature : National Academic Journal of Architecture, 2023)
In Indonesia, retirement is understood as the period when workers stop working after working for a certain period of time. They experiencing a transition phase of their life as they are doing different daily routine from the productive phase before. They are experiencing changes physically and mentally. There are urgency to make good quality environment for retired elderly in their living space. House is a good choice for elderly to be aging in place as they have sense of belonging on it. Because of that, house needs to be redesigned based on how the changes experienced by the elderlies. Here, the study will evaluate a house as in Gresik as a case study for retired elderly and give design strategy proposal to make it elderly-friendly. The method used here are descriptive method which strategies are literature review, observation and interview, problem analysis, and looking forward proposal. The main problem of the house is no adequate ventilation inside, slippery floor covering, and no outdoor space to allow elderly for being active. The strategy proposed are making outdoor space at the back as laundry area and garden, make stack-effect ventilation, and change the floor covering with anti-slip and low-pile carpet material. The existence of a garden will support the positive feelings of parents and other residents.